"Not to walk toward death." Reflections of the Roma’s experiences with the practices of the institutional system of health care - Ort Mertlová, Sandra (Romano džaniben, 2022)
The paper presents the results of an applied health research in a segregated Romani community. The author explored the attitudes of local Roma and their experiences with the institutional health care system. The text is based on interviews with ten inhabitants of a Romani settlement located in a smaller district town in Eastern Slovakia. The attitude of the selected Romani respondents toward the public health care system is embodied in their negative experiences with what they perceived as inadequate approach of doctors as well as in the ineffectiveness of suggested previous treatment. As a result of their general negative perception of the quality of health care provided in the local hospital, the Roma highlighted and practiced in many cases alternative personal health care in their home settings.